Screening and management of pulmonary arterial hypertension in systemic sclerosis - Vivek Nagaraja; Dinesh Khanna (Indian Journal of Rheumatology, 2017)
Systemic sclerosis-associated pulmonary hypertension (SSc-PH) and pulmonary arterial (PA) hypertension (SSc-PAH) are well-recognized manifestations. SSc-PH is a hemodynamic observation, and it is important to identify underlying etiology. SSc patients commonly have mixed etiology for SSc-PH due to interstitial lung disease, PAH, and left heart disease. SSc-PAH is associated with high morbidity and mortality. Early detection of PAH through routine screening improves survival in patients with SSc. Right heart catheterization is mandatory to diagnose PAH. SSc-PAH patients should be managed by a multidisciplinary team comprising of rheumatologist, pulmonologist, cardiologist, and physiotherapist. Various pharmacotherapy options to treat SSc-PAH are derived from the idiopathic PAH management. Upfront or sequential combination therapy of PAH-specific drugs seems to confer a clinical benefit compared to monotherapy. Cardiopulmonary rehabilitation should be considered as a part of the management plan. Lung transplantation is a consideration in patients who are not responding to pharmacotherapy. Although the long-term prognosis of SSc-PAH has been historically poor, the landscape is gradually changing with early detection and institution of treatment.